Synthesis, characterization, and anticancer activity of arene mono-ruthenium and heteroleptic mixed-valent diruthenium complexes - Medupe, Thato Tshwaro (Department of Chemistry, 2025)
To contribute towards the good health and well-being sustainable development goal, this project aims to synthesize and characterize organometallic arene mono-ruthenium and diruthenium complexes that have anti-neoplastic properties against the oestrogen receptor positive MCF-7, and the triple negative aggressive and invasive MDA-MB-231 human breast cancer cell lines. The preparation of diruthenium complexes led to the formation of paddlewheel-type complexes having a general chemical formula [Ru2(O2CCH3)3(R-ap)Cl] (C1 - C8). On the other hand, the preparation of mono-ruthenium complexes led to the formation of the complexes [RuCl2(η6 - C6H5OCH2CH2OH)(R)] (C10 - C12), and the novel [RuCl(η6 - C6H5OCH2CH2OH)(P(OPh)3)(SnCl3)] (C13 and C14). All complexes were characterized using spectroscopic techniques such as IR, UV-visible, 1-D and 2-D NMR. The connectivity of atoms through space as well as the solid-state structures was confirmed using X-ray crystallography. The purity of all synthesized compounds was confirmed by high-resolution mass spectrometry (HR-MS), hyphenated chromatographic techniques (LC-MS) as well as melting points. Magnetic susceptibility studies were conducted to determine and confirm the number of unpaired electrons of the paramagnetic bimetallic complexes. Due to their mixed valent Ru2(II, III) metalcore, cyclic voltammetry measurements were recorded to study the redox behaviour of the investigated complexes. The cytotoxic experiments performed against human breast MCF-7 and MDA-MB-231 cancer cells suggest that all free anilinopyridinate (R-ap) ligands do not significantly inhibit the survival growth of both cell lines, whereas coordination of these ligands to a Ru2(II, III) metal-core to form [Ru2(O2CCH3)3(R-ap)Cl] complexes (where R = CH3 or F) improves the anticancer activity against the afore-mentioned human breast cancer cells. Anilinopyridinate-type ligands were synthesized through a facile nucleophilic aromatic substitution reaction between 2-bromopyridine and the corresponding substituted anilines. The generated R-ap ligands are such that the substituent R is varied with electron-withdrawing fluorine (F) and donating methyl (CH3) substituents (L1 - L8) at different positions of the aniline ring. Synthesis of the organometallic ruthenium arene complexes was achieved via cleavage of the known ruthenium dimer [RuCl2(η6 -C6H5OCH2CH2OH)]2 with phosphine ligands. This synthetic method yielded organometallic [RuCl2(η6 -C6H5OCH2CH2OH)(R)] complexes, where R = triphenyl phosphine (C10), triphenyl phosphite (C11), trimethyl phosphite (C12). Furthermore, the reactions of C10 and C11 with SnCl2 led to the formation of the novel complexes [RuCl(η6 -C6H5OCH2CH2OH)(PPh3)(SnCl3)] (C13) and [RuCl(η6 - C6H5OCH2CH2OH)(P(OPh)3)(SnCl3)], respectively. The desired diruthenium complexes were achieved via a metathesis displacement of an acetate ligand from the precursor tetraacetate complex [Ru2(O2CCH3)4Cl] by one substituted ap ligand. This afforded stable mixed-valent diruthenium(II, III) paddlewheel complexes with a general chemical formula [Ru2(O2CCH3)3(R-ap)Cl]. Complexes [Ru2(O2CCH3)3(4-CH3ap)Cl] (C3) and [Ru2(O2CCH3)3(4-Fap)Cl] (C8) show promising anticancer effects against MCF-7 cells, having an IC50 value of 39.0 µM and 49.1 µM, respectively with favourable selectivity towards the human breast MCF-7 cells. Clonogenic assay experiments showed that C3 inhibited the ability of MCF-7 cells to survive after 7 days of monitoring cell colony formation. Western blotting analysis suggests that C3 induces double-stranded DNA breaks, observed by the increase in protein expression levels of key DNA damage response marker, ɣ-H2AX. Furthermore, C3 activates the intrinsic apoptotic signalling molecular markers, particularly caspase-9 and its downstream substrate, PARP. The stability of C3 in DMSO and RPMI media solution (used in biological assays) was confirmed by UV-visible spectroscopy. The results obtained suggest that [Ru2(O2CCH3)3(R ap)Cl] complexes are stable in DMSO for over 7 days and react rapidly with the RPMI-1640 culture media. Preliminary mechanistic studies investigating the biological molecular targets of C3 were performed by following the interactions of C3 with salmon-sperm DNA, blue script plasmid DNA and glutathione (GSH). Experiments were probed using UV-visible spectroscopic and agarose gel electrophoresis techniques. Altogether, the results obtained and presented herein in this work substantiate that the potential use of ruthenium coordination compounds and organometallic complexes in cancer therapy continues to remain a vital approach in the discovery of potent metal-based anticancer therapeutic drug leads.